PENGGUNAAN VIDEO ANIMASI PADA KETERAMPILAN MENYIMAK CERITA DONGENG SISWA KELAS II SEKOLAH DASAR - Beby Zein Rismala; Ermawati Zulikhatin Nuroh (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
The purpose of this study was to describe students' responses to the use of animated videos in listening to fairy tales for class II at SDN Bringinbendo 2, Taman District, Sidoarjo Regency. The researcher confirms that research on using animated video media in learning Indonesian on students' listening skills can be interested and active, So. Teachers must use media in order to students don't feel bored and easily understand, therefore when learning teachers don't only use the lecture method.Teachers must also be innovative in using media to be used during learning so that it can be in accordance with the desired learning, and students can also maximize learning, students are easy teachers who still tell fairy tales without using other media except thematic books that contain fairy tales